Nature as Woman in Willa Cather’s O Pioneers! - Kandel, Mukti (Literary Studies, 2021)
The present paper explores the metaphoric and symbolic meaning of feminized nature in Willa Cather’s novel O Pioneers! through the perspective of ecofeminism. The reveals that the invasion of human beings into nature is related to the patriarchy, the inequality between men and women and the binary opposition of man and nature.It primarily focuses on the characters towards nature especially in two ways – the desirable peaceful nature as a virgin and the chaotic destructive nature as a witch. This paper basically analyses how nature or land in the novel is portrayed like a virgin and a witch at the same time when the Nebraska prairie is changed into agricultural farmland. The portrayal of nature or land as stubborn or unruly land in the novel reflects the negative attitude of male characters towards nature and as such their failure to understand the Nebraska prairie especially the land of Hanover. This paper concludes that the association of women and femininity with nature in environmental discourse perpetuates patriarchal traditions and domination.